Dual-Purpose Planar Radial-Array of Rectenna Sensors for Orientation Estimation and RF-Energy Harvesting at IoT Nodes - Kumar, Manoj; Kumar, Sundeep; Sharma, Ashwani (IEEE microwave and wireless components letters, 2022)
A dual-purpose radial-array rectenna is presented as a potential sensor candidate for RF-energy harvesting (EH)-enabled Internet of Things (IoT) nodes along with orientation sensing capability. The proposed design comprises eight rectenna elements placed radially in azimuth to capture RF energy from entire 360° angular region to improve tolerance for angular misalignment and make the design orientation-oblivious. As dual-purpose, the capability to sense its own orientation with respect to the transmitter is additionally provided. Each rectenna consists of a horizontally polarized compact planar scoop-shaped antenna designed at 5.8 GHz having endfire radiation pattern with 7-dBi gain. The dc power patterns of the proposed design are calibrated and used to estimate orientation using minimum mean square error (MMSE) method. The design is verified experimentally, and the results indicate average orientation estimation error of 1.0822° with 0.9242° standard deviation and improved stability in energy-harvesting compared to single rectenna element for varying orientation of IoT nodes.